2021
DOI: 10.2147/rmhp.s298145
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Upgrading of the Industrial Structure on the Urban Employee Basic Medical Insurance Fund: An Empirical Study in China

Abstract: Background: During the transformation of economy to a high-quality level in China, industrial restructuring and upgrading have played an important role. The upgrading of the industrial structure has affected not only the development in society and economy but also other fields, thereby having great impact on social security. In recent years, with the aging of the population and economic development, the social medical insurance fund is undertaking more payment pressure. However, the existing research rarely fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…We found that patients who rely on basic medical insurance for urban workers and public health insurance have signi cantly higher medical expenses than patients with other types of insurance and completely self-paid patients. Among them, UEMI is one of the largest medical insurance plans in China, which originated in the mid-1990s (14). However, by the beginning of the 21st century, the Chinese government set up two new insurance programs : NCMI for rural residents and URMI for self-employed and unemployed urban residents (15).…”
Section: Discussionmentioning
confidence: 99%
“…We found that patients who rely on basic medical insurance for urban workers and public health insurance have signi cantly higher medical expenses than patients with other types of insurance and completely self-paid patients. Among them, UEMI is one of the largest medical insurance plans in China, which originated in the mid-1990s (14). However, by the beginning of the 21st century, the Chinese government set up two new insurance programs : NCMI for rural residents and URMI for self-employed and unemployed urban residents (15).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, temporary and self-employed workers are responsible for their social insurance premiums. In China, a majority of migrant workers from rural areas have no assets in the cities where they live, and their wages are spent on household needs, making them less risk-tolerant than local workers in multidimensional and persistent poverty [30][31][32]. In this situation, more stable and comprehensive social benefits can attract migrant workers to choose regular employment rather than self-employment and temporary employment through the increase in social welfare.…”
Section: Industrial Structure Rationalization and Employment Choices ...mentioning
confidence: 99%
“…In China, social insurance covers unemployment, pension, work injury, medical, and maternity insurance, which can guarantee a basic quality of living and reduce the income risks of workers in the event of incapacity. For regularly employed workers, enterprises and society afford most of the social security expenditures, and individuals need to pay fewer social security expenditures to receive comprehensive and stable social security [30]. However, temporary and selfemployed laborers typically do not receive employee benefits from their employers and need to pay for their social insurance, which is often prohibitively expensive for rural migrant workers.…”
Section: Social Welfare and Employment Statusmentioning
confidence: 99%
“…Conversely, mere upgrading within the tertiary industry held no bearing on the fund's income and expenditure. 2 Xie et al explored the ramifications of China's transition from a selective two-child policy to a universal two-child policy on the equilibrium of the urban employee basic medical insurance fund. Drawing from data sourced from China's 2013 and 2015 surveys, they harnessed Poisson logarithmic bilinear models, bilinear Leslie matrices, coefficient adjustment estimation, and actuarial modeling.…”
Section: Literature Review Efficiency Analysis Of Insurance Using Dea...mentioning
confidence: 99%
“…However, the primary focus of these endeavors has consistently revolved around optimizing the efficient utilization of the medical insurance fund. 2 By the end of 2021, the count of participants in employees' medical insurance surpassed 350 million, constituting around 25% of the total population covered by national medical insurance. The revenue of the employees' medical…”
Section: Introductionmentioning
confidence: 99%